Constraints Yemeni Undergraduates Face in Subtitling Audiovisual Materials - Al-Mizgagi, Essam Hassan (University of Science and Technology, Yemen, 2020)
This study attempted to investigate the potential constraints that the Yemeni undergraduates face in subtitling audiovisual materials. The challenges of English-Arabic subtitling are under three domains; linguistic, technical and attitudinal. University of Science and Technology (UST) is barely the benchmarking academic institution that gives training on subtitling. UST was perceived as an ideal place to curry out the study. A triangulation was the methodology of the paper. A questionnaire along with a test were administered and given to 38 participants. The results of the study declared that the linguistic domain is still taking the lead. The second domain was the technical challenges. The emotive or attitudinal constraints were the least challenging. The paper gave recommendations to overcome these constraints. Conclusion and recommendations of the study can be taken in other countries that undergo similar conditions.
Keywords: Audiovisual Translation; Subtitling; UST; Yemen